Aplikasi Sistem Pompa Air Tenaga PV Surya Atap 2x150 Wp Untuk Kantin Karfati Di Gedung E, Universitas Trisakti - Chairul Gagarin Irianto; Maulasukma Widjaya; ishak kasim; syamsir Abduh; Dianing Novita Nurmala Putri (Jetri : Jurnal Ilmiah Teknik Elektro, 2021)
In this study, a simple, consumable water purification system with a photovoltaic (PV) solar domestic ac motor has been designed and implemented in the Karfati canteen, E Building, Campus A, Usakti. The single-phase ac pump motor, 135Watt is used to transfer water from the storage pool to the temporary storage tank and then filter it by gravity, it is flowed through the pipe to the clean water storage tank before being distributed to ten canteen kiosk. The optimum solar panel is chosen according to the calculation of the maximum power required by the motor. The energy needs of the pump motor have been provided from solar panels and batteries through an inverter. Fixed installation of solar PV panels on the roof of building E facing 15 degrees north to optimize radiation efficiency of the system. The selection of an inverter system that matches the characteristics of the ac pump engine is developed to ensure the supply of the ac pump motor when it is started safely. Optimization of the solar PV water pump system is equipped with an array of 2 2x150 Wp PV modules, 500 VA inverters, 100 Ah batteries to supply 135 W, 220V, 50Hz pump engine power to produce clean water around 1000 liters per day in the Karfati canteen.Dalam penelitian ini, sistem penjernihan air sederhana layak konsumsi dengan motor ac domestik tenaga photovoltaic (PV) surya telah dirancang dan diterapkan di kantin Karfati Gedung E, Kampus A, Usakti. Motor pompa ac satu fasa, 135Watt digunakan untuk memindahkan air baku dari kolam penampungan ke tangki penyimpanan sementara dan selanjutnya memfiltrasinya secara grafitasi dialirkan melalui pipa ke tangki penyimpanan air bersih sebelum didistribusikan ke sepuluh kiosk kantin. Panel surya optimum dipilih sesuai perhitungan daya maksimum yang dibutuhkan motor. Kebutuhan energi motor pompa telah disediakan dari panel surya dan baterai melalui inverter. pemasangan fix panel pv surya di atap gedung E menghadap utara 15 derajat untuk mengoptimalkan radiasi efisiensi sistem. Pemilihan system inverter yang sesuai karakteristik mesin pompa ac dikembangkan untuk menjamin suplai motor pompa ac saat diasut dengan aman. Optimalisasi sistem pompa air tenaga PV surya dilengkapi dengan array dari 2 modul pv 2x150 Wp, inverter 500 VA, baterai 100 Ah mencatu daya mesin pompa 135 W, 220V, 50Hz untuk memproduksi air bersih sekitar 1000 liter per hari di kantin Karfati. .